COMPARISON OF GROWTH RATE OF Acropora cervicornis AND Echinopora horrida CORAL IN TRANSPLANTATION OF TURTLE, TABLE AND SPYDER MODELS ON BARRANG CADDI ISLAND - Ihsan Ihsan; Hartati Tamti (Jurnal Riset Diwa Bahari (JRDB), 2026)
Coral transplantation has become one of the most widely applied approaches for accelerating reef recovery in degraded marine ecosystems. This study aimed to compare the growth rate and survival of Acropora cervicornis and Echinopora horrida transplanted using Turtle, Table, and Spyder models on Barrang Caddi Island, South Sulawesi. The experiment was conducted for eight weeks at depths of 7–10 m using 60 coral fragments equally distributed among three transplantation models. Growth rate was measured based on linear extension, while survival rate and oceanographic parameters were also monitored. Data were analyzed using descriptive statistics, one-way analysis of variance (ANOVA), and Welch's independent t-test. The results showed that A. cervicornis exhibited higher growth rates than E. horrida across all transplantation models. The Turtle model produced the highest growth of A. cervicornis (2.39 mm), whereas the Table model yielded the greatest growth of E. horrida (1.77 mm). Survival rates reached 90% for A. cervicornis and 100% for E. horrida. One-way ANOVA indicated significant differences among transplantation models for both species (p < 0.05). Oceanographic conditions remained within optimal ranges throughout the study. These findings demonstrate that transplantation model configuration significantly influences coral growth and that species-specific restoration strategies are essential for improving coral rehabilitation success.